Focus on α4β2* and α6β2* nAChRs for Parkinson’s Disease Therapeutics - Pérez, Xiomara A. (2011)
L-dopa is one of the best treatments for the motor symptoms of Parkinson’s disease. However, its use is limited by the fact that it provides only symptomatic relief and chronic therapy leads to dyskinesias. There is therefore a continual search for novel therapeutic approaches. Nicotine, a drug that acts at nicotinic acetylcholine receptors (nAChRs), has been shown to protect against nigrostriatal damage and reduce L-dopa-induced dyskinesias. NAChRs may therefore represent novel targets for Parkinson's disease management. Since there are multiple nAChRs throughout the body, it is important to understand the subtypes involved in striatal function to allow for the development of drugs with optimal beneficial effects. Here we discuss recent work from our laboratory which indicates that α6β2* and α4β2* nAChRs are key in regulating striatal dopaminergic function. Experiments in parkinsonian rats using cyclic voltammetry showed that both α6β2* and α4β2* nAChR-mediated evoked-dopamine release in striatal slices is affected by nigrostriatal damage. These subtypes also appear to be important for neuroprotection against nigrostriatal damage and the nicotine-mediated reduction in L-dopa-induced dyskinesias in parkinsonian animal models. Our combined findings indicate that α4β2* and α6β2* nAChRs may represent useful therapeutic targets for Parkinson’s disease.